Plastic wood of polypropylene reinforced with wood flour: effect of the addition of compatibilizing agents from renewable resources - Poletto, Matheus (2009)
Wood plastic composites of recycled polypropylene PPr and Pinus elliottii (PIE) were developed using soybean oil, stearic acid, caprylic acid and itaconic acid grafted with polypropylene (PPgAI) as coupling agents. The composites were processed in a co-rotating twin screw extruder and injection molded. The materials were characterized by mechanical properties, thermogravimetric analysis, morphological, physical and contact angle. The results showed that soybean oil acted as a plasticizer and reduced mechanical properties of composites. On the other hand, the addition of stearic acid, caprylic acid and PPgAI resulted in an increase in flexural strength of 8, 20 and 29%, respectively, when compared to the composite without compatibilizer. The composites developed with coupling agent commonly used, polypropylene grafted with maleic anhydride (PPgAM) had a 35% increase in flexural strength. TGA results showed that the composite with soybean oil showed a reduction of thermal stability by 3% mass loss, which may be associated with more oxygen in their molecular structure and promote greater mobility of the polymer chains with increase the temperature and which may accelerate the degradation process. Composites with caprylic acid and PPgAI showed an increase above 10 ° C in temperature of 3% mass loss when compared to the composite without compatibilizer. SEM analysis showed the greater interaction between the wood flour and PPr for composites developed with PPgAI and caprylic acid. The results of contact angle showed that the incorporation of a PPgAM caused an increase in surface energy of the polymer matrix which may promote better interaction with hydrophilic wood flour.